Soybean - Biomass, Yield and Productivity 2019
DOI: 10.5772/intechopen.81544
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Epoxy Resin from Epoxidized Soybean Oil

Abstract: Epoxidized soybean oil (ESO) is the oxidation product of soybean oil with hydrogen peroxide and either acetic or formic acid obtained by converting the double bonds into epoxy groups, which is non-toxic and of higher chemical reactivity. ESO is mainly used as a green plasticizer for polyvinyl chloride, while the reactive epoxy groups imply its great potential in both the monomer synthesis and the polymer preparation fields. Functional polymers are obtained by different kinds of reactions of the ESO with co-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 114 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…1 D), indicating that heating in air increases C–OH group formation 34 , 35 and hydrogen bond formation between the molecules. On the other hand, both thermal and UV treatments intensified the SF-oil degradation by chain scission at the ester position and epoxy ring opening (decrease in 874 cm −1 peak) to form –OH and C=C chemistry 31 , 36 .
Figure 1 Infrared spectra of virgin (control), UV exposed (UV treatment) and heated (thermal treatment) SFSB oils.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 D), indicating that heating in air increases C–OH group formation 34 , 35 and hydrogen bond formation between the molecules. On the other hand, both thermal and UV treatments intensified the SF-oil degradation by chain scission at the ester position and epoxy ring opening (decrease in 874 cm −1 peak) to form –OH and C=C chemistry 31 , 36 .
Figure 1 Infrared spectra of virgin (control), UV exposed (UV treatment) and heated (thermal treatment) SFSB oils.
…”
Section: Resultsmentioning
confidence: 99%
“…13 describes different possible chemical effects of UV and O 2 oxidation agents on oil/PET chemical transformations and degraded oil/degraded PET surface interactions over time.
Figure 13 Schematic for UV/O 2 effects on SF-oil and PET interactions: UV/O 2 , temperature, and humidity yields intermolecular crosslinking and increased hydrogen bonding between oxidized oil and PET, and oil-degraded PET fractions 1 , 22 , 23 , 26 , 27 , 31 , 36 , 40 .
…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Elastic moduli of the order of 10 MPa have been reported for these polymers. [28][29][30][31] Elastic moduli of the order of 10 MPa have been reported for these polymers.…”
Section: Crosslinked Cottonseed Oil Polymer Synthesismentioning
confidence: 97%
“…21 Another study reported the synthesis of hybrid latexes from soybean oil-based waterborne polyurethane and acrylics via emulsion polymerization. [28][29][30][31] The purpose of this study was to synthesize a rigid and stable polymer using CSO. For example, styrene was copolymerized with CSO molecules.…”
Section: Introductionmentioning
confidence: 99%
“…1D), indicating that heating increases C-OH group formation [32,33] and hydrogen bond formation between the molecules. On the other hand, both thermal and UV treatments intensi ed the SFoil degradation by chain scission at the ester position and epoxy ring opening (decrease of 874 cm − 1 peak) to form -OH and C = C chemistry [29,34].…”
Section: Spin-nish Oil Degradationmentioning
confidence: 99%